2020
DOI: 10.1103/physrevd.102.103528
|View full text |Cite
|
Sign up to set email alerts
|

Helical magnetic fields from Riemann coupling

Abstract: The spectrum of energy density fluctuations, baryon asymmetry, and coherent large-scale magnetic fields are the three observables that provide crucial information on physics at very high energies. Inflation can only provide a mechanism to explain the density perturbations, and the origin of primordial magnetic fields and baryon asymmetry require physics beyond the standard models of cosmology and particle physics. In this work, we show that the mechanism that leads to primordial helical fields also leads to ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…This leads to the following crucial question: Is there a set of unique signatures that distinguish MG theories from GR? This section investigates this issue by considering three specific cases: Testing MG theories using gravitational wave (GW) observations [112][113][114][115][116], low-energy observational signatures in cosmological observations [117] and non-minimal coupling of electromagnetic fields leading to observable signatures [118][119][120].…”
Section: What Are the Observational Consequences?mentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the following crucial question: Is there a set of unique signatures that distinguish MG theories from GR? This section investigates this issue by considering three specific cases: Testing MG theories using gravitational wave (GW) observations [112][113][114][115][116], low-energy observational signatures in cosmological observations [117] and non-minimal coupling of electromagnetic fields leading to observable signatures [118][119][120].…”
Section: What Are the Observational Consequences?mentioning
confidence: 99%
“…Since both require physics beyond the standard model, there is a tantalizing possibility that the same physics can solve both problems. Recently, it was shown that non-minimal coupling of the electromagnetic field with the Riemann tensor could potentially explain magnetogenesis and baryogenesis [118,119].…”
Section: What Are the Observational Consequences?mentioning
confidence: 99%
“…One of the first works along these lines was [125], suggesting the creation of a left-handed PMF due to a change of the Chern-Simons number. Other possible mechanisms include extra dimensions [126], the coupling to the cosmic axion field [127] or an axion-like coupling [128], the Riemann tensor [129], a spectator field [84], or an inherently helical coupling [130] during Inflation in the first place. Recently, also the possibility of helicity generation via a chiral cosmological medium around the EWPT has been considered [131], however the authors found the effect to be suppressed due to the value of the baryon to entropy ratio.…”
Section: Post-inflationarymentioning
confidence: 99%
“…where it may be observed that m4 obeys a first order differential Eq. (39). With these choice of EFT parameters, the scalar Mukhanov-Sasaki equation takes the following form, ṽ (k, η)…”
Section: Solving For the Electromagnetic Mode Function And Metric Per...mentioning
confidence: 99%
“…[1], the observable quantities like scalar spectral index and tensor to scalar ratio are indeed compatible with the Planck constraints in the present EFT context where the EFT coefficients satisfy Eq. (39). Thereby using the viable value(s) of n s and A s , in particular we will consider n s = 0.9649 and ln [10 10 A s ] = 3.044 (i.e the central values of n s and A s in respect to the Planck constraints), one can determine Ḣ * and Ḧ * from Eq.…”
Section: B Reheating With Time Independent Equation Of State: Evoluti...mentioning
confidence: 99%